Hepatic copper distribution in primary biliary cirrhosis shown by the scanning proton microprobe. - Vaux, D; Watt, F; Grime, G; Takacs, J (1985)
A number of conditions are associated with abnormalities of trace metal handling by the liver. We report the application of the Oxford scanning proton microprobe to the analysis of hepatic copper in one such condition, primary biliary cirrhosis. The scanning proton microprobe analyses conventional tissue sections (5-10 micron thickness) and produces simultaneous elemental distribution maps of biologically relevant elements with a spatial resolution of 1 micron and a detection limit better than 1 ppm. We have confirmed the localisation of excess copper to periportal areas and suggest that such accumulation is confined to a proportion of periportal hepatocytes. We have also shown a close spatial correlation between regions of copper accumulation and areas of high sulphur concentration. The copper to sulphur ratio in these areas is consistent with their identity as aggregates of copper loaded metallothionein, and the scanning proton microprobe was further able to show that the aggregates contain less than 30 ppm zinc.